After Socialism (Cambridge University Press, 2003)
In this collection, twelve philosophers, historians, and political philosophers-scholars with a diverse set of disciplinary and political leanings-assess aspects of socialism in light of its recent reversals. Some of the essays consider what made the socialist project seem compelling to its advocates, examining the moral and political values that made socialism appealing to intellectuals. Others evaluate whether there are aspects of socialism that ought to be preserved, such as its quest for equality and community